PATIENTS' AND GROUP'S OF YOUNGER DENTISTS OPINION ON TREATMENT USING RUBBER DAM - Y. Morozova; E. Míšová; P. Holík; I. Voborná (Czech Dental Chamber, 2019)
Introduction: Rubber dam is an indispensable tool for dentists. It serves to provide an absolute moisture control in the oral cavity, ensures complete isolation of the treated area from other parts of the oral cavity as well as from exhaled humid air. The use of rubber dam in modern dentistry is a prerequisite for a well-done procedures mainly in the field of aesthetics and patient protection during restorative and prosthetic treatment. Objectives: The aim of the study was to find out, through original anonymous questionnaires, the opinion of patients and selected group of dentists on a treatment using rubber dam. Methodology: Two types of original questionnaires (for patients and dentists) were created. In total, 77 questionnaires were distributed to patients. The questionnaires for dentists were prepared in a printed and online version. The printed form of the questionnaire was distributed to the dentists of the Department of Operative Dentistry and Endodontics as well as the Prosthetic Department of the Institute of Dentistry and Oral Sciences of the Faculty of Medicine and Dentistry of the Palacký University in Olomouc (totally 16), who daily perform treatment requiring rubber dam use. The online questionnaire was distributed via e-mail with a link to younger dentists from private dental offices in Olomouc Region. An online questionnaire was distributed to 113 dentists. After receiving of the completed questionnaires from patients and dentists, the evaluation, statistical processing and comparison of the survey results were performed (methods of descriptive statistics, χ2 test, Mann-Whitney U-test, p = 0.05). Results: The return of patients questionnaires was 70.1%. Most of patients reported that treatment using rubber damwas more comfortable (72,2 %; χ2 test, p = 0,003) and professional (92,6 %) (χ2 test, p < 0.00001). The return rate of questionnaires from the dentists of the Institute of Dentistry and Oral Sciences was 100% and 56% from the private dentists. The total number of dentists in the group was 79. Most of the dentists (84.8%) in their daily practice use rubber dam. The length of clinical practice and gender did not have a statistically significant effect on the attitude to the use of rubber dam. There was no statistically significant difference between the use of rubber dam by dentists from the Institute of Dentistry and Oral Sciences and the private dentists (p = 0.737). Conclusions: The results of the study showed a positive attitude of the patients to the treatment using rubber dam, most of them considered this type of treatment as more pleasant and professional. Dentists of younger age group use rubber dam in their regular practice. The gender of dentists, the length of clinical practice and the type of practice (private practice, university clinic) have no statistically significant effect on the frequency of the treatment with rubber dam.